A selection-based theory of the transition from employment to entrepreneurship: the role of employer size - Simon C. Parker (Institute for the Study of Labor (IZA), 2006)
A simple occupational choice model is used to predict that entrepreneurs who found new firms are more likely to work for small than for large firms prior to start-up. The mechanism underlying the result is heterogeneous risk aversion. The model also predicts a positive association between new firm formation and previous self-employment experience. These predictions accord with previous empirical findings, but notably self-selection rather than productivity effects can explain them.
Keywords: J21; J23; J62; 330; entrepreneurship; occupational choice; firm size